2020
DOI: 10.1111/bcp.14363
|View full text |Cite
|
Sign up to set email alerts
|

Mass balance, pharmacokinetics and pharmacodynamics of intravenous HSK3486, a novel anaesthetic, administered to healthy subjects

Abstract: Aims This trial (NCT03751956) investigated the mass balance, pharmacokinetics and pharmacodynamics of HSK3486, a novel anaesthetic, in healthy subjects. Methods A single dose of 0.4 mg/kg [14C]HSK3486 was administered to six healthy subjects. Blood, urine and faecal samples were collected, analysed for radioactivity, unchanged HSK3486 and profiled for metabolites. The Modified Observer's Assessment of Alertness/Sedation (MOAA/S) scale and vital signs were closely monitored during the study. Results The mean re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
73
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(107 citation statements)
references
References 19 publications
6
73
0
Order By: Relevance
“…The plasma exposure of HSK3486 among the elderly groups (0.2, 0.3, and 0.4 mg/kg) increased gradually with the increase in dose, with no significant differences in distribution and elimination of HSK3486. This is consistent with a previous clinical pharmacokinetic study of HSK3486 with healthy adult subjects (Bian et al, 2020). After a single intravenous dose of 0.4 mg/kg HSK3486 in healthy adult subjects, the AUC, T max , t 1/2 , apparent volume of distribution during the terminal phase (Vz) and clearance were 289.2 h*ng/ ml, 0.0333 h, 1.5 h, 3.0 L/kg, and 1.4 L/h/kg, respectively, which appeared comparable to corresponding parameters from our study.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The plasma exposure of HSK3486 among the elderly groups (0.2, 0.3, and 0.4 mg/kg) increased gradually with the increase in dose, with no significant differences in distribution and elimination of HSK3486. This is consistent with a previous clinical pharmacokinetic study of HSK3486 with healthy adult subjects (Bian et al, 2020). After a single intravenous dose of 0.4 mg/kg HSK3486 in healthy adult subjects, the AUC, T max , t 1/2 , apparent volume of distribution during the terminal phase (Vz) and clearance were 289.2 h*ng/ ml, 0.0333 h, 1.5 h, 3.0 L/kg, and 1.4 L/h/kg, respectively, which appeared comparable to corresponding parameters from our study.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, there were no spontaneous reports of pain on injection with HSK3486, which is consistent with a previous study (Bian et al, 2020). Because the most common adverse reaction associated with propofol is pain on injection, with an incidence of 25-74% in adult patients (Abad-Santos et al, 2003), the absence of pain on injection with HSK3486 is considered an improvement.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Ciprofol (HSK3486) is a propofol analogue formulated in an oilin-water emulsion. Its general characteristics are similar to those of propofol 147 with a decreased frequency of pain on injection, 148 possibly because of reduced concentrations of free drug in plasma. Ciprofol is currently undergoing late-stage clinical trials for procedural sedation, 149 and trial registries indicate studies in general anaesthesia; however, none are yet reported.…”
Section: Other Novel Hypnotics On the Horizonmentioning
confidence: 87%